Implementing Project-Based Learning to Improve Tenth Graders’ Writing skill (2020)
ABSTRACT: This action research project intends to analyze how Project-Based Learning helped EFL tenth graders to improve their writing skill at a public institution in La Ceja. The information used in this project was collected through class journals, students’ artifacts, and a survey. The results of the research demonstrated that PBL approach helped students improve their writing a skill by both implementing strategies to apply PBL and to teach the writing of argumentative texts. This was achieved by making students aware of PBL and argumentative text characteristics. Besides, data revealed that students found it interesting when working through PBL as it appeared as a positive alternative in the traditional manner of ELT. Keywords: Project-Based Learning (PBL), writing skill, argumentative text, tenth grade.